1998
DOI: 10.1086/516295
|View full text |Cite
|
Sign up to set email alerts
|

Life‐Threatening Parvovirus B19–Associated Myocarditis and Cardiac Transplantation as Possible Therapy: Two Case Reports

Abstract: Parvovirus B19 infection can cause a wide spectrum of disease syndromes. Two cases of parvovirus B19 infection were identified that resulted in life-threatening myocarditis shortly after acute infection in immunocompetent individuals. The diagnosis was made with serological and polymerase chain reaction techniques. One patient was successfully treated by heart transplantation. Sequence analysis showed that the parvovirus B19 cloned from the patients' sera had 99% homology with the prototype sequence. Clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…Among these are hydrops fetalis [Anderson et al, 1988], acute and chronic arthritis [Reid et al, 1985;Naides et al, 1990;Biasi et al, 1996], acute and persistent aplastic anemia, thrombocytopenia, pancytopenia [Chorba et al, 1986;Young, 1988;Srivastava et al, 1990] and persistent infections in immunocompromised patients [Flunker et al, 1998] and also rarely in immunocompetent individuals [Cassinotti et al, 1993]. Recent case reports on B19-associated hepatitis [Hillingso et al, 1998;Pardi et al, 1998], myocarditis [Orth et al, 1997;Enders et al, 1998], and encephalitis [Umene and Nuone, 1995] have shown the increasing diversity of symptoms that can arise during B19 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Among these are hydrops fetalis [Anderson et al, 1988], acute and chronic arthritis [Reid et al, 1985;Naides et al, 1990;Biasi et al, 1996], acute and persistent aplastic anemia, thrombocytopenia, pancytopenia [Chorba et al, 1986;Young, 1988;Srivastava et al, 1990] and persistent infections in immunocompromised patients [Flunker et al, 1998] and also rarely in immunocompetent individuals [Cassinotti et al, 1993]. Recent case reports on B19-associated hepatitis [Hillingso et al, 1998;Pardi et al, 1998], myocarditis [Orth et al, 1997;Enders et al, 1998], and encephalitis [Umene and Nuone, 1995] have shown the increasing diversity of symptoms that can arise during B19 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies disclosed an association between B19 and a variety of diseases (43,48,63,80), such as arthritis (56, 77), vasculitic syndromes (19, 24, 31, 80), hepatitis (27,36,38,75,85), and neurological disorders (2, 85). Specifically, B19 infections have been observed to be associated with acute and chronic myocarditis (13,16,30,44,53,(58)(59)(60)71). Moreover, the development of endothelial and isolated left ventricle diastolic dysfunction has been associated with B19 infection (81).…”
mentioning
confidence: 99%
“…Parvovirus B19 is the causative agent of erythema infectiosum, also called fifth disease. Parvovirus B19 infection has been reported to be a rare but severe cause of myocarditis in infants and children (7,11,13). HHV-6 is the causative agent of exanthema subitum, also called sixth disease.…”
mentioning
confidence: 99%